Análise das Características do Discurso Populista de Jair Bolsonaro nas Eleições Brasileiras de 2018 - Albernaz, Vinicius (2020)
This paper seeks to analyze the main characteristics of the rise of populism in Brazil through the political discourse in the 2018 elections of President Jair Bolsonaro and its impact on Brazilian society. The methodology used in the present investigation is a theoretical, exploratory research with literature review and the use of the discourse analysis method of Vargas et al. (2018). This work is divided into three main axes: (1) the critical path of populism, (2) populism and neopopulism in Latin America and (3) the characteristics of populism of Jair Bolsonaro do Brazil. The study leads us to conclude that his speech is fundamentally characterized by a contemporary populist political discourse in Latin America.